Rational Antibiotic Use by Ordinary People in Jakarta - Sherly Tandi Arrang; Fonny Cokro; Erlia Anggrainy Sianipar (Institute for Research and Community Services, 2019)
Self-medication is defined as self treatment and self-diagnose for conditions such as cough, flu, fever, pain, stomach ulcers, worms, diarrhea, rash, and some other minor illnesses. Based on the data from Badan Penelitian dan Pengembangan Kesehatan Kementerian Kesehatan RI (2013), there were 103.860 of 294.959 households (35,2%) in Indonesia which store medicines for selfmedication (including 35,7% “Obat Keras” or “Gevaarlijk” and 27,8% antibiotics). DKI Jakarta (56,4%) is the highest province with respect to stored medicines. Some studies have found that 40-62% of antibiotics are not used properly. The inappropriate use of antibiotics can lead to antibiotic resistance risk and can be life-threatening for people in every part of the world. To address this problem, this community service was conducted to provide information about selfmedication of influenza and cough illness and to improve people’s knowledge in the proper use of antibiotics. Lecturing was chosen as the method for explaining the rational use of antibiotics and participants were requested to fill out a questionnaire. This activity was attended by 34 participants (and 32 participants filled out the questionnaire). About 13 participants (40,6%) provided correct answers to questions on the proper use of antibiotics. Twenty six participants (81,25%) said they had previously used antibiotics, 14 of them (53,85%) admitted to purchasing antibiotics without a prescription. Antibiotics are taken to treat symptoms such as runny nose, cough, sore throat, fever, and other conditions. A total of 7 participants (26,92%) admitted taking antibiotics with dosage modification and 8 participants (30,77%) switched one type of antibiotics with another type of antibiotics. Based on the results, we concluded that people did not have sufficient knowledge about the rational use of antibiotics. We suggested that counseling about the proper use of antibiotics should be improved.